أحكام الوصية الواردة على العقار في ظـل التشريع الجزائري - إسماعيل عماري, حليمة سعد الله (My University, 2019)
لقد تطرق المشرع الجزائري لطرق إكتساب الملكية في القانون المدني وذلك في المواد 775 إلى 777 وحسب نص المادة 775 منه نجد أن المشرع قد أحال أحكام الوصية إلى قانون الأحوال الشخصية، وبالرجوع إلى قانون الأسرة نجده قد نظم موضوع الوصية في الكتب الرابع منه في المواد184 الى201 من قانون الأسرة حيث بين تعريفه و مقدارها وأطرافها وحدد شروطها وكيفية أثباتها، وفي ما يتعلق بالصيغة أن تكون بلفظ دال على القبول موافقا للإيجاب صريحا أو دلاله بعد موت الموصى ويكون صدورها من مختار لها. نجد أن المشرع الجزائري من خلال قانون الأسرة اعتمد في تشريعه للوصية على الشريعة الإسلامية حيث حدد شروط صحة الوصية، كما توصلنا إلى التعرف على مبطلات الوصية من جانب الموصى والموصى له والموصى به، وفي ما يتعلق في أثبات الوصية وتنفيذها بالإضافة إلى شكلها لم يفصل المشرع الجزائري في ذلك، بل تركها للفقه الإسلامي. The Algerian legislator has dealt with the methods of acquiring property in the civil law in Articles 775 to 777 and according to the text of Article 775 thereof, we find that the legislator referred the provisions of the will to the Personal Status Law, and by referring to the Family Code, we find that the subject of the will was organized in the fourth books of it in Articles 184 to 201 of Family law where between As he explained its definition, its amount and its parties, and defined its conditions and how to prove them, and with regard to the formula, it should be in a wording indicating acceptance in agreement with the explicit offer or its connotation after the death of the recommended and its issuance by a chosen one
مذكرة ماستر
Keywords: إكتساب الملكية في القانون المدني وذلك في المواد 775 إلى 777 وحسب نص المادة 775 منه نجد أن المشرع قد أحال أحكام الوصية إلى قانون الأحوال الشخصية،; provisions of the will to the Personal Status Law, and by referring to the Family Code, we find that the subject of the will was organized in the fourth books of it in Articles 184 to 201 of Family law where